2015
DOI: 10.1039/c5cp00215j
|View full text |Cite|
|
Sign up to set email alerts
|

Study of structures and thermodynamics of CuNi nanoalloys using a new DFT-fitted atomistic potential

Abstract: Shape, stability and chemical ordering patterns of CuNi nanoalloys are studied as a function of size, composition and temperature. A new parametrization of an atomistic potential for CuNi is developed on the basis of ab initio calculations. The potential is validated against experimental bulk properties, and ab initio results for nanoalloys of sizes up to 147 atoms and for surface alloys. The potential is used to determine the chemical ordering patterns of nanoparticles with diameters of up to 3 nm and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 46 publications
2
8
0
1
Order By: Relevance
“…Based on these results, we concluded that vacancies in the d shell, the deformation energy of the Cu 32 shell, and the cohesive energy of the M 6 core are useful for discussing and predicting the Cu 32 M 6 structure. These factors also play important roles in determining the structure and stability of other combinations of two metal elements; for instance, the present results suggest that the Cu–Ni binary metal cluster has a core–shell structure with Ni atoms in the core because Ni has a d 8 s 2 electron configuration. Indeed, a theoretical study using the Gupta potential reported that such a core–shell structure is stable . In discussing very large metal clusters/particles, however, the results for the relatively small systems considered here are not very useful, and the factors discussed are insufficient because some other factors such as the size-mismatching effect and the size dependency of the cohesive energy become more important.…”
Section: Resultsmentioning
confidence: 90%
“…Based on these results, we concluded that vacancies in the d shell, the deformation energy of the Cu 32 shell, and the cohesive energy of the M 6 core are useful for discussing and predicting the Cu 32 M 6 structure. These factors also play important roles in determining the structure and stability of other combinations of two metal elements; for instance, the present results suggest that the Cu–Ni binary metal cluster has a core–shell structure with Ni atoms in the core because Ni has a d 8 s 2 electron configuration. Indeed, a theoretical study using the Gupta potential reported that such a core–shell structure is stable . In discussing very large metal clusters/particles, however, the results for the relatively small systems considered here are not very useful, and the factors discussed are insufficient because some other factors such as the size-mismatching effect and the size dependency of the cohesive energy become more important.…”
Section: Resultsmentioning
confidence: 90%
“…It is known that the Cu–Ni bulk alloys present a miscibility gap for temperatures below 600 K . However, in recent works, it is suggested that in nanoparticles with sizes below 10 nm, the driving forces dominating segregation are much weaker, thus eventually lowering the miscibility gap to below room temperature . Hence, it is a plausible hypothesis that the metallic Cu obtained for negative voltages gets dissolved again in the Cu–Ni solid solution at room temperature owing to the narrow pore walls and the high surface area‐to‐volume ratio of the investigated material.…”
Section: Resultsmentioning
confidence: 99%
“…A last case demonstrating the problematic use of cohesiveenergies instead of actual solid-state interatomic bond-energies involves modeling of phase segregation and transition temperatures in Cu-Ni truncated-octahedra. Previous studies that focused on few overall compositions only [6,37,38] predicted an asymmetric off-centre Cu/Ni Janus-like compositional configuration (JA) as the most stable at relatively low temper atures, which was found also by STEM/EDX measurements [39]. Indeed, according to our preliminary FCEM/ CBEV computations that involve fewer concentration variables when combined with the coarse-grained layer model, CGLM [40], this configuration is obtained for almost all compositions (excluding the very dilute ones) when the bondenergies of Cu and of Ni are used as input (E b , table 1).…”
Section: Nanophase Segregation (Separation) Diagrams Of Cu-ni Nanoparmentioning
confidence: 99%